Interactive learning media: javanese children songs for third-grade students - Kusuma, Natara Krisna; Laila, Alfi; Wenda, Dhian Dwi Nur (Jurnal Ilmiah Pendidikan Dasar, 2024)
Children’s songs are one of the materials in the Javanese language subject that students must master. The lack of use of learning media during Javanese language lessons on children’s songs has resulted in students struggling to grasp the material. This research aims to develop interactive learning media for the Javanese language subject in third grade, focusing on children’s song material. This research employs the Research and Development (R&D) method and the ADDIE development model:  analysis,  design, development, implementation, and evaluation. The subjects of this study are third-grade students from Sambirobyong 2 Elementary School, Kayen Kidul District, Kediri Regency, for the 2023/2024 academic year. The validity results, based on assessments from material and media experts, scored 88% and were deemed acceptable, while the practicality test results scored 96%. Based on the research findings of Javanese Children's Songs for Third-grade Students, the validity and practicality of the developed product were obtained.  Implications of this research interactive learning media for children’s song material in the third-grade Javanese language subject is suitable for classroom learning activities.